Penyuluhan dan Pelatihan Tentang Pembuatan Sistem Irigasi Lep Pipa Pada Jaringan Irigasi Air Tanah Dalam Di Dusun Arungan Bali Desa Akar Akar Kabupaten Lombok Utara - I Dewa Gede Jaya Negara; Anid Supriyadi; Atas Pracoyo (Universitas Mataram, 2020)
At present in the dry land of Akar Akar Village, the government has built no less than 22 ground water pumping wells since 1990. on the land. Arungan Bali as one of the locations of dry land with potential land that is pivot and sandy, 6 hours to 8 hours per hectare of land. The irrigation period is long and very wasteful of ground water, requiring very expensive costs. To overcome this, it is necessary to develop a network of existing JIAT with a lep pipe system to improve irrigation in land plots. Based on the results of field tests the pipe lep irrigation system can provide land faster than the existing JIAT system. For that, the pipe-pipe irrigation network needs to be restored to the farming community and given training, so that the plantation method is easy for the community to imitate. This dedication is carried out by extension methods and training in making pipeline irrigation in dry land. In counseling discussions and questions and answers, while in the training carried out the manufacture of irrigation networks in plots of land. The results of this dedication show that, the Arungan Bali farmer community has gained knowledge about plantations and can create a pipe irrigation network in a plot of land. The community can make a land network because an example already exists in the land around the residents' land. 30% of the ways that already exist.